The Development of Inflation in Lebanon – The Causes and Impacts on the Country's Economy - Bednáriková, Nina; De Castro, Tereza; Abdallah, Kareem Issam; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
Lebanon, the former ‘Switzerland of the Middle East’, is enduring an unprecedented economic meltdown, battling several overlapping crises simultaneously. Yet it faces another serious problem – hyperinflation. The consumer prices of goods and services escalated by hundreds or thousands of percent, and the annual inflation rate surged to 154% in 2021. This bachelor’s thesis aims to evaluate the development of the inflation in Lebanon, focusing on the recent period from 2019 to the present day. For this purpose, I formulated two research questions: What are the primary causes of high inflation in Lebanon? And what impacts does it have on the Lebanese economy? The key findings suggest that the build-up of inflation is rooted in strong dependency on massive dollar inflow and a lack of adequate economic policies. Furthermore, the results show a significant increase in retail prices across all categories, accompanied by real income decline and deterioration of purchasing power. Additionally, my research outcomes confirmed that a rise in inflation induces an increase in poverty.
Vedoucí práce: Tereza De Castro
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses